Evaluation of Soil Organic Carbon Stock in Coastal Sabkhas under Different Vegetation Covers - Ebrahem M. Eid; Muhammad Arshad; Sulaiman A. Alrumman; Dhafer A. Al-Bakre; Mohamed T. Ahmed; Hanan Almahasheer; Amr E. Keshta (Journal of Marine Science and Engineering, 2022)
There has been increasing focus on conserving coastal ecosystems as they have been recognized as high ecosystem carbon stocks and are in the process of land conversion. The present study aims to examine how different vegetation covers impact the soil organic carbon (SOC) stock in coastal sabkhas. To this end, the study was carried out at ten sampling sites represent ten sabkhas in Saudi Arabia’s southern Red Sea coast for two main goals: (1) to examine the vertical distribution of SOC content, SOC density, and the soil bulk density (SBD) based on different vegetation covers, and (2) to assess these locations’ SOC stocks. This study posits that sabkhas with different vegetation covers had distinct parameters specified above. Significant SBD differences were observed in sabkhas with different vegetation covers, with the lowest mean values of sabkhas having >75–100% vegetation cover and the highest mean values of sabkhas having 0–25% vegetation cover. The studied sabkhas also showed significant difference in the total means of SOC density, SOC content, and SOC stock in terms of different vegetation covers, with the highest mean values of sabkhas having >75–100% vegetation cover and the lowest mean of sabkhas having 0–25% vegetation cover. The present study is the first to focus on Saudi Arabia’s sabkha blue carbon stocks and its results can help add to the literature on sabkhas carbon stock, thus aiding relevant government agencies working towards sabkhas management, encouraging public awareness regarding sabkhas conservation stocks, and their part in climate change mitigation.